The minimum thickness of a multilayer porcelain restoration required for masking severe tooth discoloration - Niloofar Shadman; Saeideh Gorji Kandi; Shahram Farzin Ebrahimi; Maryam Azizi Shoul (Wolters Kluwer Medknow Publications, 2015)
Background: Although studies have shown that porcelain veneers are very efficient for treating discolored teeth, they did not address in particular the minimum thickness of a multilayer IPS e.max Press (IvoclarVivadent, Schaan, Liechtenstein) restoration required to mask discolored tooth. The aim of this study was to determine the minimum thickness of a multilayer porcelain restoration required for masking severe tooth discoloration. Materials and Methods: A total of 24 disk-shaped multilayer specimens were prepared from IPS e.max Press with the diameter of 13 mm and four different thicknesses (core/veneer: 0.4/0.4 mm, 0.5/0.5 mm, 0.6/0.6 mm and 0.8/0.7 mm). Two backgrounds, C4-shade body porcelain and an opaque background from the selected IPS e.max ceramic itself were fabricated to mimic a discolored or stained natural tooth structure and to determine the masking ability. After applying the resin cement layer (Panavia F2.0) with 0.01 mm thickness on each background, all specimens were measured on both background using a spectrophotometer and values of LFNx01, aFNx01 and bFNx01 were calculated to determine the color differences (ΔEFNx01ab). One-way ANOVA and post-hoc tests of specimen average one-to-one comparison (Tukey HSD) were conducted and P ≤ 0.05 was set as the level of significance. Results: ΔEFNx01ab of all groups were within the range of the clinically acceptable color difference (ΔE ≤3.3), thus all the groups could mask the C4 background even group 1 with only 0.8 mm thickness. A trend was shown in the results as by increasing the thickness, ΔEFNx01ab is was decreased. The mean ΔE FNx011FNx01aFNx01b between different thicknesses were statistically significant (P < 0.05) only between group 4 with groups 1 and 2, respectively. Conclusion: Within the limitations of this study, all studied thicknesses could mask the C4 background. However, the minimum thickness of a multilayer porcelain restoration (IPS e.max Press) required for masking severe tooth discoloration was 0.8 mm.